The problem in the evaluation of the efficacy and safety of nonsteroidal anti-inflammatory drugs - N. V. Chichasova (Современная ревматология)
The review gives data on the safety of nimesulide used for the treatment of chronic joint diseases. The first-line treatment at its any stage for joint diseases is nonsteroidal anti-inflammatory drugs (NSAIDs). Questions have recently arisen of the safety of nimesulide; however, epidemiological findings and clinical experience confirm a positive benefit/risk profile of nimesulide in the treatment of acute pain. The International Consensus Meeting (Vienna, 2014) noted that the risk of severe adverse hepatic NSAID reactions was low and the rate of liver damage associated with nimesulide was completely similar to that observed with other NSAIDs. There are data available in the literature on the rate of serious adverse liver reactions to different NSAIDs and paracetamol. The rate of such reactions to all NSAIDs per million patientyears was 1.55 and that to nimesulide was 1.88. The members of the International Consensus Group concluded that nimesulide, if properly used, remained a valuable and safe drug for the treatment of various conditions, characterized by the presence of acute inflammatory pain, by virtue of the rapid onset of analgesic action and an evidence-based positive benefit/risk profile. The long successful experience with nimesulide in our country suggests that the agent may be successfully used to treat chronic and acute pain (including dysmenorrhea) in a daily dose of 200 mg/day. The safety profile of the drug is quite satisfactorily for all adverse reactions typical of NSAIDs, including its negative effect on the liver.